Investigating the effect of fiber arrangement on tensile properties of two-dimensional hybrid braided composite rods - Ali Shaker Soureh; Majid Safar Johari; Sajjad Khadem Ilkhechi (Scientific Reports)
Abstract Braided composites are gaining attention in the most industrial applications. To design rods with optimal tensile properties against combined loads, experimental studies were conducted to investigate the effect of using axial yarn and core in different categories on the tensile properties of braided reinforced composite rods. In this study, six types of braided composite rods with different arrangements of braid components (axial yarn or core type) were produced using glass and polyester fibers with epoxy resin as the matrix. The elastic modulus, ultimate tensile strength, and work of fracture of these rods were tested, and the experimental elastic modulus of samples were compared with previously developed models. Moreover, comparing the stress-strain results of the samples revealed that the produced hybrid samples demonstrate pseudo-ductile tensile behavior, showing varying trends as the type of reinforcement is altered. The results indicate that using a double-layer triaxial braid as reinforcement for the composite can increase the elastic modulus up to 13% compared to the similar single-layer sample. Additionally, employing a double-layer triaxial braid as reinforcement for the composite leads to a greater work of fracture. However, in terms of ultimate tensile strength, biaxial braid reinforcement demonstrates better performance in reinforcing the composite rods.